The Effect of Exercise on the Early Stages of Mesenchymal Stromal Cell-Induced Cartilage Repair in a Rat Osteochondral Defect Model. - Shoki Yamaguchi; Tomoki Aoyama; Akira Ito; Momoko Nagai; Hirotaka Iijima; Junichi Tajino; Xiangkai Zhang; Wataru Kiyan; Hiroshi Kuroki (PLoS ONE)
The repair of articular cartilage is challenging owing to the restriction in the ability of articular cartilage to repair itself. Therefore, cell supplementation therapy is possible cartilage repair method. However, few studies have verified the efficacy and safety of cell supplementation therapy. The current study assessed the effect of exercise on early the phase of cartilage repair following cell supplementation utilizing mesenchymal stromal cell (MSC) intra-articular injection. An osteochondral defect was created on the femoral grooves bilaterally of Wistar rats. Mesenchymal stromal cells that were obtained from male Wistar rats were cultured in monolayer. After 4 weeks, MSCs were injected into the right knee joint and the rats were randomized into an exercise or no-exercise intervention group. The femurs were divided as follows: C group (no exercise without MSC injection); E group (exercise without MSC injection); M group (no exercise with MSC injection); and ME group (exercise with MSC injection). At 2, 4, and 8 weeks after the injection, the femurs were sectioned and histologically graded using the Wakitani cartilage repair scoring system. At 2 weeks after the injection, the total histological scores of the M and ME groups improved significantly compared with those of the C group. Four weeks after the injection, the scores of both the M and ME groups improved significantly. Additionally, the scores in the ME group showed a significant improvement compared to those in the M group. The improvement in the scores of the E, M, and ME groups at 8 weeks were not significantly different. The findings indicate that exercise may enhance cartilage repair after an MSC intra-articular injection. This study highlights the importance of exercise following cell transplantation therapy.